(untitled) (Research, Society and Development, 2021)
Introduction: Physiotherapy goes through moments of historical and curricular evolution that culminate today in the search for the best way to train professionals who are more general and close to the needs of society. However, the curricular changes that the profession goes through are not always able to supply what the student needs for a more complete training. Objective: To evaluate student practice before and after using an educational video about the physical therapy physical examination of the critical patient at the bedside. Methods: Single-arm clinical trail study with undergraduate students (n = 25) from the last year of Physiotherapy at a Public University in the State of Pará, from August to December 2018. The protocol consisted of the inclusion of a video educational in the students’ routine and their evaluative complement through the Miniex instrument. Results: Average evaluation time of the pre and post-video phases of 9.2 ± 3.5 and 13.4 ± 1.9 (p < 0.0001). Improvement in the pre and post-video scores in the items of the Miniex (p < 0.0001); skill in physical examination 2.2 ± 1.2 and 7.4 ± 1.2, humanistic qualities/professionalism 2.0 ± 1.3 and 6.3 ± 2.4, clinical reasoning 2.3 ± 1.4 and 7.5 ± 1.3, guidance skills 2.6 ± 1.6 and 7.3 ± 1.4, organization/efficiency 2.0 ± 1.0 and 6.7 ± 2.1 and general clinical competence 2.4 ± 1.4 and 7.4 ± 1.3. Conclusion: The proposed educational video proved to be an efficient tool in the Physiotherapy student practice scenario.